MODELING OF THE DYNAMIC PROCESS RELEASE OF STUCK DRILLING TOOLS BY HYDRO-PULSE METHOD - Levchyk, K. H.; Shcherbyna, M. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
A technical solution is proposed for the elimination the grabbing of drilling tool, based on the use of energy due to the circulation of the drilling fluid. The expediency eliminating the grabbing drilling tool using the hydro-impulse method is substantiated. A method of drawing up a mathematical model for the dynamic process of a grabbing string of drill pipes in the case of perturbation of hydro-impulse oscillations in the area of the productive rock layer is developed. The law of longitudinal displacements arising in the trapped string is obtained, which allows choosing the optimal geometrical parameters of the passage channels and the frequency rotational of shutter for these channels. Recommendations for using this method for practical use have been systematized.